Pengaruh "Empowerment" Di Kalangan Guru Terhadap Pencapaian Sekolah - Azizah, Md. Salleh (1997)
The study attemps to find out how empowerment and it's four factors (job design, organisation structure, authority and reward) can influence school achievement. Data were collected via questionnaire from 403 samplings which consist of principal, senior assistant and teacher. The finding showed that empowerment and only it's three factors (job design, authority and reward) are significantly related to school achievement. The finding also showed that job design is the best predictor in carrying out empowerment.